Efektivitas antibakteri cuka sari apel terhadap pertumbuhan bakteri Escherichia coli dan Staphylococcus aureus secara in vitro - Aryasa, I Wayan Tanjung; Artini, Ni Putu Rahayu (Jambura Journal of Chemistry, 2025)
The chemical name for vinegar is acetic acid, which is derived from the Latin word acetum. Acetic acid, ethane acid, or vinegar is a chemical compound of organic acids and is the most important carboxylic acid in commerce, industry and laboratories known as acidity. And the taste of food. However, keep in mind that vinegar can act as a disinfectant. A well-known type of vinegar is apple cider vinegar. With the above background in mind, this study formulates the question of how apple cider vinegar inhibits the growth of E. coli and Staphylococcus aureus. The analysis of this study was performed in the form of a quasi-experimental experiment, ie by comparing the inhibitory power of apple cider vinegar with the control of Escherichia coli and Staphylococcus aureus growth, and the design of a pure control group after the test. Thing. Based on the results of the studies conducted, the diameters of the inhibition zones formed in Escherichia coli of foreign apple cider vinegar, Indonesian apple cider vinegar, and local apple cider vinegar are 12.33 ± 0.12 mm, 2.21 ± 0.12 mm. It is shown that. And 7.42 ± 0.09 mm. The diameters of the inhibition zones formed on the yellow staphylococci of foreign apple cider vinegar were 14.56 ± 0.46 mm, 0.00 ± 0.00 mm and 10.36 ± 0.27 mm for Indonesian apple cider vinegar and local apple cider vinegar, respectively. Hmm. From this, we can conclude that apple cider vinegar has an antibacterial effect against Escherichia coli and Staphylococcus aureus.